Bed, surface elevation and ice thickness measurements derived from Radar acquired during the ICEGRAV-2013 airborne geophysics campaign ... - Ferraccioli, Fausto; Corr, Hugh; Jordan, Tom; Forsberg, René; Matsuoka, Kenichi; Diez, Anja; Olesen, Arne; Ghidella, Marta; Zakrajsek, Andrés; Robinson, Carl; King, Owen (Polar Data Centre, Natural Environment Research Council, UK, 2018)
This dataset contains bed, surface elevation and ice thickness measurements from the Recovery/Slessor/Bailey Region, East Antarctica. Radar data was collected using the 150MHz PASIN radar echo sounding system (Corr et al., 2007) deployed on a British Antarctic Survey (BAS) Twin Otter during the ICEGRAV-2013 airborne geophysics campaign (Forsberg et al., 2018). Data is identified by flight and are available in both Geosoft database (.gdb) and ASCII file formats (.xyz). ...